Variability of soil enzyme activities and nutrients with forest gap renewal interacting with soil depths in degraded karst forests - Zhao, Ying; Han, Zhen; Zhang, Guangqi; Chen, Danmei; Zang, Lipeng; Liu, Qingfu; Guo, Yun; Xie, Peiyun; Chen, Hongchun; He, Yuejun (Ecological indicators, 2024)
•Gap renewal interacting with soil depths significantly affected soil enzyme activities and nutrients.•Association of enzyme activities and nutrients varying with gap renewal and soil depths.•Soil enzymes modified CNP stoichiometry regulating soil fertility for karst forest gap renewal. Forest gaps serve as crucial starting points for forest self-renewal. Within these gaps, soil enzymes play an essential role in driving nutrient transformation and species renewal. However, how forest gap renewal regulates soil fertility through soil enzyme across various soil depths remains unclear. This investigation delved into the dynamics of soil enzymes and nutrients within karst forest gaps at four developmental age stages: Infancy (<10 years), Youth (10–20 years), Middlescence (20–30 years), and Elder (>30 years) across different soil depths (0–10 cm, 10–20 cm, and 20–30 cm). The study determined the contents of CNP and the activities of soil enzymes such as polyphenol oxidase, catalase, protease, and alkaline phosphatase. Two-way ANOVA was employed to assess the variations in gap ages and soil depths, along with their interaction. Redundancy analysis (RDA) was used to reveal the correlations between soil enzyme activities and CNP fertility indicators. The results indicated that gap age significantly influenced the activities of alkaline phosphatase, polyphenol oxidase, and protease, as well as the contents of total and available nitrogen, phosphorus, and organic carbon, alongside the ratios of N/P, C/N, and C/P. Catalase activity, however, did not vary significantly with gap age, although soil depth influenced these parameters, excluding total phosphorus and the C/N ratio. Notably, in the 0–10 cm soil layer, alkaline phosphatase activity, total nitrogen, available nitrogen, and organic carbon contents significantly increased with gap age increase, followed by a significant decrease after the middlescence stage. In the 10–20 cm and 20–30 cm soil layers, Alkaline phosphatase and polyphenol oxidase activities, along with N/P and C/N ratios initially decreased and then increased with gap age increase. During the Infancy, Youth, and Middlescence stages, Polyphenol oxidase and protease activities, CNP contents, as well as N/P and C/P ratios generally decreased with soil depth increase or after an increase in the 10–20 cm soil layer. RDA highlighted the variational positive and negative correlations between soil enzyme activities and CNP fertility indicators across soil depths during forest gap renewal, with explanatory rates ranging from 88.05 % to 94.67 % across soil layers. Overall, this study suggests that forest gap renewal significantly influences soil enzymes, CNP content and stoichiometry, modifying soil CNP content through stoichiometric regulation across different soil depths, and ultimately sustaining soil fertility via soil enzymes.